N-[bis(2,4,6-trimethylphenoxy)phos-phinoyl]-P,P,P-tris(2,4,6-trimethyl-phenoxy)phosphazene - Höekelek, T; Akduran, N; Begeç, S; Kiliç, A; Kiliç, Z (Int Union Crystallography, 2000)
The title compound, C45H55NO6P2, consists of an acyclic P=N-P(O) monophosphazene chain and five bulky 2,4,6-trimethylphenoxy side groups which predominantly determine the molecular shape. Although the P-N single [1.586 (3) Angstrom] and P=N double [1.517 (3) Angstrom] bonds are significantly different from each other, both are substantially shorter than the ideal P-N single bond. The P-N-P angle [146.0 (2)degrees] corresponds to the upper limit reported for acyclic phosphazene derivatives in the literature.
Keywords: Phosphorus-Nitrogen-Compounds; Trichloro-N-Dichlorophosphorylmonophosphazene; Chain Linear Phosphazenes; Crystal-Structure; Side-Groups; Aminolysis; Cl2p(O).N=Pcl3; Conformation